Conservação de energia elétrica: um enfoque em consumidores residenciais - Silva, Paulo Roberto Mendes da (2008)
This work investigates the most used forms of electric energy conservation, especially in Brazil, without neglecting the power quality aspect, emphasizing residential loads. Among the investigated issues, the technological is a very important one since it comprises the application of efficient equipment. However, it is not forgotten the human actions, with great application in the residential point of view. Power quality practical studies involving lightning residential loads are also presented. These studies were carried out with a lab prototype capable of simulating power quality problems, such as momentary and long-term voltage sags. Electrical parameters were monitored trough a power quality analyzer equipment - DRANETZ 4300. The results show that the consumer may not acquire a product (compact efficiency light in this case) according to the manufacturer specifications, being very far from the label specifications. The main objective was, therefore, to study the efficiency energy concepts actions and energy savings, associating them to the cost reduction related to electrical energy and the continuous improvement in cost management taking into account the power quality aspect.